Representasi Bullying dalam Film The Emoji Movie - Aletheia Imanuel; Septia Winduwati (Kiwari, 2023)
The Emoji Movie is a 2017 Sony Pictures animated film directed by Tony Leondis. The purpose of this study is to dissect the representation of bullying in the form of discrimination and intimidation and the search for identity in the main character in The Emoji Movie and to find out the message that The Emoji Movie wants to convey to the audience. This study uses a qualitative approach using Roland Barthes' semiotic analysis technique in which there are elements of verbal bullying that trigger the search for the main character's identity in The Emoji Movie. The results obtained from this research are that in this film the meaning of bullying is constructed, where bullying should have a negative meaning but becomes a positive meaning in this film, as the starting point for triggering the formation of the main character's self-confidence in the search for his identity. But, basically a person's resilience and the meaning of bullying for each individual is different. Other people's opinions on our behavior in society can be positive or negative depending on our response and our meaning. The Emoji Movie merupakan film animasi produksi Sony Pictures tahun 2017 disutradarai oleh Tony Leondis. Tujuan dari penelitian ini untuk membedah representasi bullying dalam bentuk diskriminasi dan intimidasi dan pencarian jati diri pada tokoh utama dalam film The Emoji Movie dan untuk mengetahui pesan yang ingin disampaikan melalui film The Emoji Movie kepada penonton. Penelitian ini menggukan pendekatan kualitatif dengan teknik analisis semiotika Roland Barthes yang di dalamnya terdapat unsur-unsur bullying verbal yang menjadi pemicu pencarian jati diri tokoh utama dalam film The Emoji Movie. Hasil dari penelitian ini yaitu film ini mengkonstruksikan makna bullying, dimana bullying yang seharusnya bermakna negatif tetapi menjadi makna positif dalam film ini, sebagai awal mula pemicu terbentuknya kepercayaan diri tokoh utama dalam pencarian jati dirinya. Tetapi pada dasarnya resiliensi seseorang dan pemaknaan bullying untuk setiap individu berbeda-beda. Pendapat orang lain atas perilaku kita di masyarakat dapat menjadi hal yang positif maupun negatif tergantung respon kita dan pemaknaan kita.